2020
DOI: 10.18510/hssr.2020.8522
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychological Capital on Workplace Wellbeing and Employee Engagement Among Saudi Workforce

Abstract: Purpose of the study: The purpose of the study is to find out the complex relationship between psychological capital (PsyCap), workplace wellbeing (WWB), and employee engagement (E.E.) among the working class of Saudi Arabia. Methodology: The study which used a cross-sectional quantitative research design made use of three structured, validated questionnaires to collect the required data. Data were randomly collected online from a sample of 395 respondents. The respondents belonged to varying demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 84 publications
2
6
0
Order By: Relevance
“…The study’s findings were in line with Eskildsen and Dahlgaard (2000) and Tang et al (2019), showing the influence of psychological capital on employees’ job satisfaction unlike the study of Idris and Manganaro (2017) that reported no significant relationship between psychological capital and employees’ job satisfaction. Other studies such as Abosaif (2018), Aljaghthami and Noormala (2016), Ibrahim and Amari (2018), and Saad Alkahtani et al (2020) also confirmed the positive impact of psychological capital on various constructs. Extant literature has also revealed psychological capital is narrowly related to their work performance (Avey et al, 2008), positivity, and creativity (Rego et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The study’s findings were in line with Eskildsen and Dahlgaard (2000) and Tang et al (2019), showing the influence of psychological capital on employees’ job satisfaction unlike the study of Idris and Manganaro (2017) that reported no significant relationship between psychological capital and employees’ job satisfaction. Other studies such as Abosaif (2018), Aljaghthami and Noormala (2016), Ibrahim and Amari (2018), and Saad Alkahtani et al (2020) also confirmed the positive impact of psychological capital on various constructs. Extant literature has also revealed psychological capital is narrowly related to their work performance (Avey et al, 2008), positivity, and creativity (Rego et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…Given that, and due to the importance of the development of human capital worldwide and particularly in Saudi Arabia, it is noted that a limited number of researches were carried to investigate its effect on various constructs. For example, Alkahtani et al (2020) revealed in their study that there is a positive connection between psychological capital, workplace well-being, and employees' engagement. Another study of Abosaif (2018) reported that psychological capital predicts the faculty members' quality of life at Altaif University.…”
Section: Introductionmentioning
confidence: 99%
“…Based on psychological capital theory, psychological capital could help employees deal with various life pressures and dedicate their energies to work [ 65 ]. In this way, they will improve their work engagement and feel more workplace well-being [ 66 ]. Therefore, if individuals possess high levels of psychological capital, they will perform more positively and be more hopeful, making psychological capital an indicator of teachers’ career prosperity [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, few studies have been executed on entrepreneurial intention and traits. Instead, most Saudi studies have been dedicated to entrepreneurial education, psychological capital, and recognized institutions, among related features [29][30][31]. Having consistent and validated procedures for recognizing entrepreneurial traits among healthcare students may be indispensable for the development of future entrepreneurial healthcare members.…”
Section: Introductionmentioning
confidence: 99%